Occupational Commitment in Private Higher Education Sector: Work-Life Balance, Job Burnout and the Mediating Effect of Supportive Culture - Sofiah Kadar Khan; Bibiana Chiu Yiong Lim; Yusman Yacob (International Journal of Business and Society, 2022)
This study aims to study the effect of occupational commitment (OC) toward work-life balance (WLB) and job burnout with the mediating effect of a supportive culture (SC) in the context of employees in the private higher education sector in Malaysia. This paper adopted a purposive sampling technique among academics in private higher education in Malaysia. A quantitative approach using Partial Least Square PLS-SEM (Structural Equation Modelling) method was applied to analyse the data. The results show that OC is positively related to SC and SC has a high potential for lowering job burnout. The study also found that SC positively affects WLB. Furthermore, SC was found to elucidate the effect between OC, WLB and job burnout among employees in the private higher education sector. The study has two major theoretical implications. The study reaffirms the existing theory by demonstrating that OC, WLB, and job burnout are significantly related through support culture as a mediator. In addition, the study extends the existing theory by putting forward that understanding the effect of OC on employees' work behaviour in the private higher education research model can account for the variations in different sectors and contexts.